Prognostic significance of the FAN score in patients with advanced urothelial carcinoma treated with enfortumab vedotin monotherapy - Hiromu Horitani; Atsunari Kawashima; Yu Ishizuya; Yoshiyuki Yamamoto; Takuji Hayashi; Shunsuke Inoguchi; Yuki Horibe; Nesrine Sassi; Yujiro Hayashi; Takeshi Ujike; Koichi Tsutahara; Mototaka Sato; et al. (Japanese Journal of Clinical Oncology, 2026)
Abstract Objective To evaluate the prognostic significance of the Fib-4 index, ALBI and NLR (FAN) score, a composite score comprising the fibrosis-4 index, albumin-bilirubin score, and neutrophil-to-lymphocyte ratio, in patients with advanced urothelial carcinoma treated with enfortumab vedotin (EV) monotherapy. Methods This multicenter retrospective study included 164 patients with advanced urothelial carcinoma who received EV monotherapy following prior systemic therapy. Patients were classified into three groups (0, 1, and 2–3) based on the FAN score, and progression-free, cancer-specific, and overall survival (OS) outcomes were evaluated. Results The proportion of patients with FAN scores of 0, 1, and 2–3 were 26.8% (n = 44), 40.2% (n = 66), and 32.9% (n = 54), respectively. Median progression-free survival (PFS) was 8.1, 5.7, and 3.8 months across FAN score groups. A significant difference was observed between the FAN 0 and 2–3 groups (Holm-adjusted P = .025). Median cancer-specific survival (CSS) was 17.5, 12.2, and 7.2 months and differed significantly across groups (Holm-adjusted P = .012). OS showed a similar significant decline (Holm-adjusted P = .013). Multivariable analysis confirmed the FAN score as an independent prognostic factor for OS, CSS, and PFS. Furthermore, adding the FAN score to a model comprising conventional clinical factors improved prognostic accuracy for both CSS and OS (ΔC-index for CSS = 0.067, bootstrap P < .001; ΔC-index for OS = 0.057, bootstrap P < .001). Conclusions The FAN score is a simple and clinically useful prognostic tool that may improve risk stratification in patients receiving EV monotherapy for advanced urothelial carcinoma.